Quarant’anni nella giustizia minorile: intorno a un libro di Melita Cavallo - Costantino, Ludovica; Santoro, Angela (Il sogno della farfalla, 2017)
The article is inspired by a book by judge Melita Cavallo, entitled Si fa presto a dire famiglia (It’s easy to say family) (Rome-Bari 2015), where, on the basis of her own experience in juvenile justice, the author describes how Italian families have changed in the last fourty years. The book depicts a judge, a woman and a mother who faces difficult, ever-changing situations and who, by doing so, realizes that laws are not enough on their own, rather, they require to be upported by a strong human identity that cares for the problems of others, and should involve people. From the stories the author narrates, the picture of diseased families emerges, where children are the main victims, who are often negated and annulled by their mothers who, in turn, have been annulled in their human identity. Thus, the need for greater attention to such phenomena, with interventions of prevention and treatment aimed at restoring a healthy human identity.